A large-scale dataset of barley, maize and sorghum variety identification using dna fingerprinting in Ethiopia - Kosmowski, Frederic; Ambel, A.; Tsegay, A.H.; Negawo, Alemayehu T.; Carling, J.; Kilian, Andrzej; Central Statistics Agency, Ethiopia (MDPI, 2021)
The data described in this paper were part of a large-scale nationally representative household survey, the Ethiopian Socioeconomic Survey (ESS 2018/19). Grain samples of barley, maize and sorghum were collected in six regions in Ethiopia. Variety identification was assessed by matching samples to a reference library composed of released improved materials, using approximately 50,000 markers from DArTseq platforms. This data were part of a study documenting the reach of CGIAR-related germplasms in Ethiopia. These objective measures of crop varietal adoption, unique in the public domain, can be analyzed along with a large set of variables related to agro-ecologies, household characteristics and plot management practices, available in the Ethiopian Socioeconomic Survey 2018/19.